Protein sorting from endosomes to the TGN - Buser, Dominik P.; Spang, Anne (Frontiers in Cell and Developmental Biology, 2023)
Retrograde transport from endosomes to the trans-Golgi network is essential for recycling of protein and lipid cargoes to counterbalance anterograde membrane traffic. Protein cargo subjected to retrograde traffic include lysosomal acid-hydrolase receptors, SNARE proteins, processing enzymes, nutrient transporters, a variety of other transmembrane proteins, and some extracellular non-host proteins such as viral, plant, and bacterial toxins. Efficient delivery of these protein cargo molecules depends on sorting machineries selectively recognizing and concentrating them for their directed retrograde transport from endosomal compartments. In this review, we outline the different retrograde transport pathways governed by various sorting machineries involved in endosome-to-TGN transport. In addition, we discuss how this transport route can be analyzed experimentally.